Effects of substitution of black glutinous rice flour for wheat flour on batter and cake properties - Itthivadhanapong, P. (2018)
The effect of substitution of black glutinous rice flour for normal wheat flour on batter and cake properties was determined. Black glutinous rice flour was used to substitute 30, 50, 70 and 100% of wheat flour in a control cake formulation. Experimental data showed that pasting temperature, peak viscosity, final viscosity, breakdown and setback of all black glutinous rice and mixes flour samples were less than that of 100% wheat flour. Substitution of black waxy rice flour influenced the batter viscosity, resulting less viscous batters as the proportion of black rice flour increased. Moreover, the results also showed that the substitution of glutinous rice flour caused an increase in specific gravity and trended to decrease the specific volume of cake. The color of crust and crumb cake progressively became darker as the level of black glutinous rice substitution increased. According to texture profile analysis, the cake with black glutinous rice flours had greater firmness, gumminess and chewiness values compared to the control cake with no added black glutinious rice flour. Hedonic sensory tests revealed that the cake prepared with black waxy rice flour had similar (P>0.05) flavor, taste, texture, and overall acceptable scores to that of the control sample. Subsequently, the functional properties of black waxy rice may lead it to be a nutritionally and economicaly important to the bakery industry.